DC motor controlled based on microcontroller - Fatinah, Abdul Ghani (2012)
The DC motor uses in drive system in many industrial applications are still significant. In this project, the DC motor controlled based on microcontroller PIC 18F4550 is proposed. The controller will control the speed and direction of the DC motor. The microcontroller will generate the PWM (Pulse Width Modulation) signal and use to control the speed of motor. The DC drive will be used to control the direction of the DC Motor. The analysis of the drive performance is also carry out in this project. The experiment showed that the motor speed can be controlled via microcontroller from zero to maximum speed easily at low cost since PIC has built in programmable timers, ports and interruption where no extra hardware is needed.